Mechanistic Insight Into the Roles of Integrins in Osteoarthritis - Jin, Hongfu; Jiang, Shigang; Wang, Ruomei; Zhang, Yi; Dong, Jiangtao; Li, Yusheng (Frontiers in Cell and Developmental Biology, 2021)
Osteoarthritis (OA), one of the most common degenerative diseases, is characterized by progressive degeneration of the articular cartilage and subchondral bone, as well as the synovium. Integrins, comprising a family of heterodimeric transmembrane proteins containing α subunit and β subunit, play essential roles in various physiological functions of cells, such as cell attachment, movement, growth, differentiation, and mechanical signal conduction. Previous studies have shown that integrin dysfunction is involved in OA pathogenesis. This review article focuses on the roles of integrins in OA, especially in OA cartilage, subchondral bone and the synovium. A clear understanding of these roles may influence the future development of treatments for OA.